Long-term effects of motivational interviewing vs. traditional counseling on dog owners’ adherence to veterinary dental home care: a three-year follow-up study - Enlund, Karolina Brunius; Jönsson, Birgitta; Abrahamsson, Kajsa H.; Pettersson, Ann (Frontiers in Veterinary Science, 2024)
Periodontal disease is one of the most common health issues in dogs. However, disease is largely preventable by eliminating dental plaque, best achieved by daily tooth brushing. Unfortunately, owner adherence is low to the recommendation of daily tooth brushing in dogs.Objective: This study aimed to evaluate the impact of various communication strategies, traditional advice (TA) versus motivational interviewing (MI), and compare them to a control group receiving no additional communication (CG), on dog owners' performance of dental home care and the oral health of their dogs. Methods: The study was conducted as a longitudinal clinical intervention study spanning three years, and involved 75 dog owners with young dogs who were randomly assigned to one of three groups: TA, MI, or CG. Intervention groups received annual telephone consultations based on their assigned methodology. A questionnaire was administered twice to all groups, and the dental health of the dogs was assessed at the study's conclusion. Result: Tooth brushing frequency demonstrated a significant increase in the MI group compared to the CG group (p<0.01), albeit with a relatively low occurrence of daily brushing among owners. Dental health assessment revealed a significantly lower plaque index in the MI group compared to the CG group (p<0.05), and a lower calculus index in the TA group compared to the CG group (p<0.01). No statistically significant differences were observed between the MI and TA groups in terms of dental health.Regular veterinary communication appears to have a positive influence on dog owner adherence to veterinary recommendations concerning dental care in dogs. Communication with veterinarians (MI and traditional advice) improved owner knowledge, attitude, and decreased frequency of not brushing. Although dental health parameters improved, the effect size was small, suggesting the complexity of adherence. Personalized calls to dog owners offer potential for dental health improvement, warranting further comparison of MI with traditional advice.